From the carolingian technopaegnia to the medieval «clerecía rabínica». new horizons in medieval literature illuminated by comparative poetry - Gonzalez-Blanco García, Elena (Cuadernos de Filología Clásica. Estudios Latinos, 2011)
The concept of «mester de clerecía» is exposed here as a broad phenomenon whose origins are in Medieval non-quantitative latin poetry, in which, after the lost of the vowels quantity, the number of syllables is determining. This work will analyze two texts from a comparative point of view: a latin poem composed in tetrastichs of pentadecasyllables during the carolingian period, attributed to Paulin of aquilea, which reflects the initial status of medieval narrative poetry «a sílabas contadas»; and a castilian poem composed in the 13th century in «cuaderna vía» written by a Jewish author: the Coplas de Yosef. Both have a common source: the story of Joseph narrated in the book of Genesis. However, the literary procedures used by both authors, as well as the final results are very different. The contrastive analysis of the two texts make us determine the ideology present in each of them and also make us pose key questions related to the concept of «mester de clerecía», its definition, limits and evolution.
Keywords: Story of Joseph; Mester de clerecía; cuaderna vía; Paulinus of aquilea; Medieval poetry